2016
DOI: 10.1002/jmv.24639
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment of CMV‐reactive cellular immunity during pregnancy

Abstract: Cytomegalovirus (CMV) is the most common congenital viral infection. Mother-to-child transmission can cause severe child disability. Intact CMV-specific cell-mediated immunity (CMI) was shown to prevent uncontrolled replication in healthy individuals. This study aimed to determine whether CMV-specific CMI is impaired in pregnant women, thus potentially increasing the overall risk for active CMV replication and transmission. CMV-specific CMI in peripheral blood of 60 pregnant women was determined using T-Track®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…This is particularly relevant for the monitoring of CMV-specific CMI in immunocompromized patients. Accordingly, we recently demonstrated the benefit of measuring the response to both T-activated® IE-1 and pp65 antigens in terms of assay sensitivity, in clinical studies assessing CMV-specific CMI during pregnancy [53], in hemodialysis patients [49] and in renal transplant recipients (submitted).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant for the monitoring of CMV-specific CMI in immunocompromized patients. Accordingly, we recently demonstrated the benefit of measuring the response to both T-activated® IE-1 and pp65 antigens in terms of assay sensitivity, in clinical studies assessing CMV-specific CMI during pregnancy [53], in hemodialysis patients [49] and in renal transplant recipients (submitted).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that interferon (IFN)-γ is crucial in antiviral control and all cellular assays that are CE-marked for in vitro diagnostics determine CMV-specific IFN-γ production [7,8,9,10,11]. Data on other cytokines, however, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Performance of T-Track ® CMV has been recently characterized [38]. A recent study demonstrated its high sensitivity in evaluating changes in CMV-specific CMI during and after pregnancy [39]. …”
Section: Introductionmentioning
confidence: 99%